(untitled) (Research, Society and Development, 2021)
Extreme rainfall events are the cause of several tragedies and disorders. Urban drainage is essential to combat these problems. Urban galleries are not always able to absorb all the demand arising from these events, so the greatest ally of these is natural soil. Few studies aim to quantify the contribution of this medium to drainage in urban centers. This study aimed to estimate the necessary dimensioning of storm sewers to solve these problems, using the soil parameters of infiltration rate and the volumetric capacity of rainwater retention, analyzing the water balance in a commercial and academically important area of ​​the city of Recife PE. Granulometry and simple ring infiltration tests were used to model the water balance in the regions of natural terrain in the predetermined area. The soil proved to be a good conductor, being able to absorb daily rainfall of almost 49mm in its own physical limit. The difficulty encountered was the low rates of natural terrain available in the region - 17% of the total, reducing its performance. It was found that approximately 410 l/s would be needed as the necessary flow from the main network of this urban area, to absorb most of the extreme precipitation events.